Impact of mastectomy on quality of life in female patients with breast cancer in the Gaza Strip: a cross-sectional study. (March 2019) - Alaloul, Enas; Elshami, Mohamedraed; Khader, Esraa; Abu Nemer, Huda; Alhelu, Alaa; Awad, Israa; Baraka, Heba; Böttcher, Bettina; Elessi, Khamis
Abstract: Background: For patients with breast cancer, the quality of care following mastectomy should be designed with long-term goals to ensure the physical and psychosocial wellbeing of survivors. This study explores the impact of mastectomy on the quality of life of breast cancer survivors in the Gaza Strip. Methods: This cross-sectional study involved the only two oncology centres of the Gaza Strip. In total, 173 patients who had undergone mastectomy were chosen using convenience sampling. Upon their arrival at the oncology centres (a minimum of 3 months after mastectomy), the patients completed face-to-face questionnaires made up of five sections: sociodemographic data, physical, psychological, and social wellbeing, and family dynamics. Data were collected from August, 2015, to September, 2016. SPSS software (version 21) was used for data analysis. Ethics approval was obtained from the Palestinian Ministry of Health. Findings: The mean age at data collection was 51·0 (SD 10·0) years. In total, 73·0% (126 of 173) had low educational achievements (below secondary level), 91·0% (157) were unemployed, and 20·8% (36) had a first-degree relative with breast cancer. Two-thirds (133) had undergone radical mastectomy, and 17·0% (29) had breast-conserving surgery. Evaluation of the negative impacts of mastectomy showed that psychological wellbeing was the most affected domain (66·4%; 115), followed by physical wellbeing (52·2%; 90), social wellbeing (44·2%; 77), and family dynamics (49·2%; 85). Following mastectomy, 57·2% (99), 48·6% (84), and 42·8% (74) of patients experienced fatigue, early menopausal symptoms, and sleep disturbances, respectively. Feeling worried was the most common psychological complaint (52·6%; 91). Furthermore, 55·5% of patients (96) experienced financial impacts (eg, some mentioned that treatment expenses were drawn from very basic living and household funds), and 59·0% (102) had decreased day-to-day activity (physical activity for the household that would usually be carried out on a regular basis, such as chores). Interestingly, 95·4% (165) were worried about divorce owing to their surgery. Interpretation: The fear of divorce found in this study demonstrates the insecurity of women in society in Gaza. However, this study could not validate the reality of such fears (for example, determine the proportion of women who get divorced following mastectomy). Involving the patient's family in the treatment process is important to promote social wellbeing. Improving holistic medical care for survivors of breast cancer in the Gaza Strip is essential. Funding: None.